Metformin’s effects on varicocele, erectile dysfunction, infertility and prostate-related diseases: A retrospective cohort study - Tseng, Chin-Hsiao (Frontiers in Pharmacology, 2022)
Objectives: To investigate the risk of varicocele, erectile dysfunction (ED), infertility, prostatitis, benign prostate hyperplasia (BPH) and prostate cancer associated with metformin use. Materials and methods: A total of 261,838 males, mean age 52.39 years (SD: 11.39), with a new-onset type 2 diabetes mellitus in 1999-2009 were identified from Taiwan’s National Health Insurance. Among them, 175,171 were metformin initiators [metformin (＋)] and 86,667 were non-metformin initiators [metformin (－)] in the initial 12-month prescriptions of antidiabetic drugs. Follow-up started after the initial 12-month prescriptions. Outcomes were followed up until December 31, 2011. Intention-to-treat (ITT) and per-protocol (PP) hazard ratios comparing metformin (＋) to metformin (－) were estimated by Cox regression incorporated with the inverse probability of treatment-weighting using propensity scores. Results: The median follow-up time ranged 5.55–6.82 years in metformin (－) and 4.36–5.17 years in metformin (＋) for different outcomes in ITT analyses. The respective median follow-up time in PP analyses ranged 2.20–2.61 years in metformin (－) and ranged 3.99–4.65 years in metformin (＋). In the ITT analyses, for metformin (－), the incidence rates (per 100,000 person-years) of varicocele, ED, infertility, prostatitis, BPH and prostate cancer were 26.42, 455.89, 22.82, 590.23, 4226.19 and 141.69, respectively; and the respective incidence rates for metformin (＋) were 25.65, 488.10, 32.60, 510.30, 3685.66 and 116.57. The hazard ratios (95% confidence intervals) comparing metformin (＋) to metformin (－) in the ITT analyses were 0.960 (0.784–1.174) for varicocele, 1.077 (1.026–1.130) for ED, 1.368 (1.116–1.676) for infertility, 0.887 (0.849–0.927) for prostatitis, 0.883 (0.868–0.899) for BPH and 0.878 (0.802–0.961) for prostate cancer. The hazard ratios for the respective outcomes in the PP analyses were 0.845 (0.662–1.078), 1.350 (1.264–1.441), 1.396 (1.078–1.808), 0.800 (0.756–0.846), 0.875 (0.855–0.895) and 0.613 (0.548–0.686). Conclusion: Metformin use in patients with type 2 diabetes mellitus is associated with a neutral effect on varicocele, a higher risk of sexual dysfunction (ED and infertility) and a reduced risk of prostate-related health (prostatitis, BPH and prostate cancer).